2012
DOI: 10.1121/1.3699532
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between ultrasonic guided wave velocities and bone properties in bovine tibia in vitro

Abstract: Correlations between ultrasonic guided wave velocities and bone properties were investigated in bovine tibia in vitro. The velocities of the first arriving signal and the slow guided wave, termed VFAS and VSGW, along the long axis of the tibia were measured at 200 kHz in 20 bovine tibiae using the axial transmission technique. VFAS yielded significant negative correlation coefficients of −0.54 to −0.66 with the bone properties. In contrast, VSGW yielded strong positive correlation coefficients of 0.68–0.84. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…64 Ultrasound has been exploited to study long bones using the so- The application of GWs to study long bones is quite recent but 81 the results so far are quite interesting. Nicholson of A 0 and S 0 modes with cortical thicknesses in bovine tibiae [9]. 91 Ta et al found that the L(0, 2) mode was quite sensitive to the 92 thickness change in the cortex [10].…”
mentioning
confidence: 98%
“…64 Ultrasound has been exploited to study long bones using the so- The application of GWs to study long bones is quite recent but 81 the results so far are quite interesting. Nicholson of A 0 and S 0 modes with cortical thicknesses in bovine tibiae [9]. 91 Ta et al found that the L(0, 2) mode was quite sensitive to the 92 thickness change in the cortex [10].…”
mentioning
confidence: 98%
“…13 The first version of the axial transmission approach consisted in recording the time-of-flight of the earliest component of the signal recorded at the receivers, the so-called first arriving signal (FAS). [14][15][16][17][18] In subsequent developments, a multiple frequency approach in which FAS velocity is measured at different frequencies has also been described. 9,19,20 A different approach, based on a more complete analysis of the recorded time signals, consists in detecting one or more particular guided modes which are then identified by coupling the experimental analysis to a model of the waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…If the couple ( 0 , k 0 ) is located in zone I, the associated peak intercepts the  = 0 line. Thus following Eq (18),. the limit between the two zones corresponds to  k less than 4/(M L).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 It has been reported that the FAS velocity can characterize both material properties and thickness of cortical bones. 7 It has also been found that the slow guided wave (SGW) arriving after the FAS can provide enhanced characterization of both material properties and thickness of cortical bones. 8 In contrast to the FAS, the SGW has shown to essentially behave as the lowest order antisymmetrical (A0) Lamb wave independently of the cortical thickness-to-wavelength ratio with the velocity increasing with increasing thickness.…”
Section: Introductionmentioning
confidence: 99%